Climate Smart Agriculture - Knowledge Sharing Day 2 - International Center for Tropical Agriculture (2015)
CIAT hosted a Climate Smart Agriculture Knowledge Sharing Day & Tools Bazaar in Nairobi on 20 May 2015. Here, participant Michael Ochieng' Okumu explains a CSA prioritisation tool developed by the Kenyan Ministry of Agriculture & Fisheries.